Electric field controlled gradient index chalcogenide glass materials and methods of making and controlling the same

CN118344004BActive Publication Date: 2026-10-16NINGBO UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410412655.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2026-10-16
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

现有制备梯度折射率玻璃的方法主要有固体扩散法、溶胶-凝胶扩散法等,但是上述的制备方法大多局限于折射率的二维(2D)梯度分布,并且步骤复杂、耗时长、能耗高

Benefits of technology

[0017] 1) This invention introduces a gradient refractive index chalcogenide glass material by adding element A to introduce low-valence cations as migrating ions, adding element M to introduce high-valence cations, and adding element X to introduce anions, thus obtaining a gradient refractive index chalcogenide glass material with a certain ionic conductivity. The preparation method of this invention's gradient refractive index chalcogenide glass material is simple and efficient, making it a key material for realizing the application of small-weight, small-volume, low-cost, and high-efficiency gradient refractive index devices. It can meet different optical requirements in devices of the same volume and mass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118344004B_ABST
    Figure CN118344004B_ABST
Patent Text Reader

Abstract

The electric field controlled gradient refractive index chalcogenide glass material disclosed in the application is composed of A, M and X elements, wherein A element is selected from at least one of Li, Na, K and Ag, M element is selected from at least one of B, Si, Ge, Sn, P, As, Ga and Sb, and X element is selected from at least one of O, S, Se and Te, wherein the mole percentage of A, M and X elements is respectively 10% to 80%, 5% to 50% and 10% to 50%. Under the action of the applied external electric field, low-valence cations are directionally migrated, and the network structure formed by high-valence cations and anions remains unchanged, so that ion concentration gradient is formed along the electric field direction in the material, and then the refractive index gradient is formed. The refractive index gradient caused by the different size of the applied external electric field is different, so that the refractive index gradient of the prepared chalcogenide glass material can be adjusted and controlled through the electric field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical chalcogenide glasses, specifically relating to an electric field-controlled gradient refractive index chalcogenide glass material and its preparation and control methods. Background Technology

[0002] Based on the direction of refractive index change, gradient-index (GRIN) glasses can be classified into axial, radial, radial-axial hybrid, and spherical gradient-index materials, allowing for the control of refractive index and optical path in different directions according to the application scenario. Existing methods for preparing gradient-index glasses mainly include solid-state diffusion and sol-gel diffusion methods. However, these methods are mostly limited to a two-dimensional (2D) refractive index gradient distribution, and are complex, time-consuming, and energy-intensive. Furthermore, optical zoom structures based on materials with fixed refractive index gradients remain relatively complex, heavy, and bulky, making it difficult to meet the application requirements of miniaturization, lightweighting, and integration. Simultaneously, because the refractive index gradient of the material is fixed, it cannot be changed after preparation, hindering the rapid response of the optical system under different application conditions. In conclusion, although gradient-index glass materials have a very broad application prospect, currently, no technology or process can achieve adjustable and controllable refractive index gradients in the prepared glass material to meet the needs of applications under different conditions. Summary of the Invention

[0003] The technical problem this invention aims to solve is to address the shortcomings of existing technologies by providing an electric field-controlled gradient refractive index chalcogenide glass material and its preparation and control methods. In this invention, under the influence of an applied external electric field, low-valence cations migrate directionally, while the network structure formed by high-valence cations and anions remains unchanged. This creates an ion concentration gradient along the electric field direction within the chalcogenide glass material, thereby forming a refractive index gradient. Depending on the magnitude of the applied external electric field, the resulting ion concentration gradient in the chalcogenide glass material varies, thus causing different refractive index gradients. This allows for the adjustment and controllability of the refractive index gradient of the prepared chalcogenide glass material through an electric field.

[0004] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: an electric field-controlled gradient refractive index chalcogenide glass material, which is composed of three elements: A, M, and X. Element A is selected from at least one of Li, Na, K, and Ag; element M is selected from at least one of B, Si, Ge, Sn, P, As, Ga, and Sb; and element X is selected from at least one of O, S, Se, and Te. The molar percentage of element A is 10% to 80%, the molar percentage of element M is 5% to 50%, and the molar percentage of element X is 10% to 50%. The sum of the molar percentages of elements A, M, and X is 100%.

[0005] This invention introduces low-valence cations as migrating ions by adding element A (at least one of Li, Na, K and Ag), introduces high-valence cations by adding element M (at least one of B, Si, Ge, Sn, P, As, Ga and Sb), and introduces anions by adding element X (at least one of O, S, Se and Te), thereby obtaining a gradient refractive index chalcogenide glass material with a certain ionic conductivity.

[0006] The inventors of this application unexpectedly discovered that: 1) the gradient refractive index chalcogenide glass material of the present invention has an ionic conductivity of 0.001 S / cm to 5 S / cm at room temperature, and can achieve rapid migration of low-valence cations under the action of an electric field; 2) a large gradient refractive index (Δn up to 0.1) can be achieved by applying a relatively low external electric field (0.05 V to 10 V); 3) by changing the magnitude or direction of the applied external electric field, the magnitude and direction of the refractive index gradient can be controlled in real time and efficiently, and the refractive index of the material returns to no gradient when the external electric field is removed, while the gradient refractive index can be achieved again when the external electric field is applied again.

[0007] The chalcogenide glass material of this invention uses low-valence cations as charge carriers, possessing a certain ion transport capability. Therefore, under the influence of an external electric field, the gradient refractive index can be variably adjusted, satisfying different optical requirements in devices of the same volume and mass. When an external electric field is applied, only small-diameter low-valence cations migrate within the chalcogenide glass material, exhibiting high mobility. This results in extremely fast refractive index adjustment and recovery, enabling the achievement of multiple refractive index gradients in a short time. Furthermore, when adjusting the gradient refractive index of this chalcogenide glass material using an external electric field, only a relatively low field is required, enabling the application of lightweight, compact, low-cost, and high-efficiency gradient refractive index devices.

[0008] The method for preparing the above-mentioned electric field-controlled gradient refractive index chalcogenide glass material includes the following steps:

[0009] (1) Based on the determined molar percentage of each element in the chalcogenide glass material, calculate and weigh each raw material, and then mix the raw materials evenly.

[0010] (2) The uniformly mixed raw materials are vacuum sealed in a quartz tube, and then the quartz tube is placed in a swing furnace and melted at 250℃~950℃ for 1h~40h. Then the quartz tube is quenched with compressed air for 0.5min~3min, and then annealed at 150℃~350℃ for 5h~30h. After cooling with the furnace, the quartz tube is opened to obtain bulk chalcogenide glass material.

[0011] (3) Cut and polish the bulk chalcogenide glass material into the desired shape.

[0012] Preferably, in step (2), the quartz tube is melted at 450℃~850℃ for 10h~25h, then quenched with compressed air for 1min~2min, and then annealed at 200℃~300℃ for 10h~20h.

[0013] The above-described method for controlling the gradient refractive index of chalcogenide glass materials using electric field control involves adding conductive units to the polished surface of the bulk chalcogenide glass material. An external electric field of 0.05V to 10V is applied to the bulk chalcogenide glass material through these conductive units, achieving a gradient refractive index with a maximum refractive index difference Δn of 0.1. By adding conductive units to the polished surface of the bulk chalcogenide glass material, electric field control of the refractive index gradient can be achieved with a relatively low external voltage. The control method is simple, low-cost, does not require an extremely high external electric field, offers high safety, and has low power consumption. This invention enables low-cost, low-power, and high-efficiency electric field control of the refractive index gradient of chalcogenide glass materials.

[0014] Preferably, the conductive unit comprises a conductive silver paste layer and an electrode. The conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and the electrode is attached to the surface of the conductive silver paste layer. The electrode is externally connected to a voltage of 0.05V to 10V.

[0015] Preferably, the voltage of the external electric field applied to the bulk chalcogenide glass material through the conductive unit is 0.1V to 5V, which can obtain the desired gradient refractive index.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1) This invention introduces a gradient refractive index chalcogenide glass material by adding element A to introduce low-valence cations as migrating ions, adding element M to introduce high-valence cations, and adding element X to introduce anions, thus obtaining a gradient refractive index chalcogenide glass material with a certain ionic conductivity. The preparation method of this invention's gradient refractive index chalcogenide glass material is simple and efficient, making it a key material for realizing the application of small-weight, small-volume, low-cost, and high-efficiency gradient refractive index devices. It can meet different optical requirements in devices of the same volume and mass.

[0018] 2) The gradient refractive index chalcogenide glass material of the present invention has an ionic conductivity of 0.001 S / cm to 5 S / cm at room temperature. It can achieve a large gradient refractive index with a maximum refractive index difference Δn of 0.1 under a low external electric field. Moreover, the refractive index gradient of the material can also be synchronously generated and eliminated when the external electric field is repeatedly applied and removed, that is, the refractive index gradient can be controlled at any time. At the same time, by controlling the direction of the external electric field, refractive index gradients in different directions can also be achieved.

[0019] 3) The gradient refractive index control method of this invention is simple and low-cost. This control method overcomes the problem of the inability to control the refractive index of currently prepared chalcogenide glass materials. By utilizing a relatively low external electric field, a high concentration gradient of low-valence cations can be induced within the chalcogenide glass material, thereby achieving control over the refractive index gradient of the prepared chalcogenide glass material. This control method can achieve real-time and efficient control of the gradient refractive index of chalcogenide glass materials by changing the direction and intensity of the applied external electric field, meeting the needs of different application scenarios and representing a gradient refractive index control strategy with great application potential. Attached Figure Description

[0020] Figure 1 A top view of the chalcogenide glass material prepared in Example 1 when an external electric field is applied;

[0021] Figure 2 The image shows the XRD crystal diffraction data of the chalcogenide glass material prepared in Example 1.

[0022] Figure 3 Nyquist plot of the chalcogenide glass material prepared in Example 1;

[0023] Figure 4 The transmission spectrum of the chalcogenide glass material prepared in Example 1;

[0024] Figure 5 The graph shows the Δn vs. Voltage variation of the chalcogenide glass material prepared in Example 1. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0026] Example 1: Electric field controlled gradient refractive index Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 A method for preparing chalcogenide glass materials includes the following steps:

[0027] (1) Mix the raw materials Ag powder, Ge powder, Ga powder and S powder evenly in a molar ratio of 0.1:0.3:0.1:0.5;

[0028] (2) The uniformly mixed raw materials were vacuum-sealed in a quartz tube, and then the quartz tube was placed in a swing furnace and melted at 650°C for 10 hours. Then, the quartz tube was quenched with compressed air for 0.5 minutes, and then annealed at 180°C for 10 hours. After cooling in the furnace, the quartz tube was opened to obtain Ag. 0.1 Ge 0.3 Ga 0.1 S 0.5 Bulk chalcogenide glass materials;

[0029] (3) Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 The bulk chalcogenide glass material is cut into cuboids and its top and bottom surfaces are polished.

[0030] Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 Bulk chalcogenide glass material is placed on an insulating pad, in Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 A conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and then an electrode is attached to the surface of the conductive silver paste layer. The electrode is connected to a 5V voltage via a wire. Figure 1 For Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 A top-view schematic diagram of a bulk chalcogenide glass material under an applied external electric field. Figure 1 In the diagram, 1 is an insulating pad, and 2 is Ag coated with a conductive silver paste layer. 0.1 Ge 0.3 Ga 0.1 S 0.5 Bulk chalcogenide glass material, 3 is the electrode, 4 is the wire.

[0031] Ag prepared in Example 1 0.1 Ge 0.3 Ga 0.1 S 0.5 The properties of bulk chalcogenide glass materials are as follows:

[0032] The ionic conductivity at room temperature is 0.1 S / cm;

[0033] Mechanical properties: Ag 0.1 Ge 0.3 Ga 0.1 S 0.5 It is in a glassy state, and after its upper and lower surfaces are polished, the thickness of the bulk material is 0.5mm, which has good light transmission ability;

[0034] Gradient refractive index: Maximum refractive index difference Δn = 0.1.

[0035] Ag prepared in Example 1 0.1 Ge 0.3 Ga 0.1 S 0.5 It is a glass material, and no obvious diffraction is observed in the XRD pattern (see...). Figure 2This indicates that the method can prepare glassy chalcogenide bulk materials; moreover, the material has an ionic conductivity of 0.1 S / cm at room temperature (see...). Figure 3 Furthermore, the material itself exhibits good transmittance in the range of 2.5μm to 25μm (see...). Figure 4 These factors all contribute to the influence of the applied electric field on the low-valence cations within the material, thus the material exhibits a maximum refractive index difference of 0.1 under a 5V applied electric field (see...). Figure 5 Furthermore, the high ionic conductivity provides a solid foundation for achieving electric field-controlled refractive index gradients in chalcogenide glasses. By simply coating the polished material surface with conductive silver paste, low-cost, low-power, and high-efficiency electric field-controlled refractive index gradients can be achieved.

[0036] Example 2: Electric field controlled gradient refractive index Li 0.3 B 0.1 P 0.3 S 0.3 A method for preparing chalcogenide glass materials includes the following steps:

[0037] (1) Mix the raw materials Li2S powder, B powder, P powder and S powder evenly in a molar ratio of 0.3:0.2:0.6:0.3;

[0038] (2) The uniformly mixed raw materials were vacuum-sealed in a quartz tube, which was then placed in a gyratory furnace and melted at 850°C for 5 hours. The quartz tube was then quenched with compressed air for 0.5 minutes, followed by annealing at 300°C for 10 hours. After furnace cooling, the quartz tube was opened to obtain Li. 0.3 B 0.1 P 0.3 S 0.3 Bulk chalcogenide glass materials;

[0039] (3) Li 0.3 B 0.1 P 0.3 S 0.3 The bulk chalcogenide glass material is cut into cuboids and its top and bottom surfaces are polished.

[0040] Li 0.3 B 0.1 P 0.3 S 0.3 Bulk chalcogenide glass material is placed on an insulating pad, in Li 0.3 B 0.1 P 0.3 S 0.3 A conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and then an electrode is attached to the surface of the conductive silver paste layer. The electrode is connected to a voltage of 7.5V through a wire.

[0041] Li prepared in Example 20.3 B 0.1 P 0.3 S 0.3 The properties of bulk chalcogenide glass materials are as follows:

[0042] The ionic conductivity at room temperature is 0.001 S / cm;

[0043] Mechanical properties: Li 0.3 B 0.1 P 0.3 S 0.3 It is in a glassy state, and after its upper and lower surfaces are polished, the thickness of the bulk material is 0.5mm, which has good light transmission ability;

[0044] Gradient refractive index: Maximum refractive index difference Δn = 0.08.

[0045] Example 3: Electric field controlled gradient refractive index Na 0.3 Sb 0.1 Sn 0.2 Se 0.4 A method for preparing chalcogenide glass materials includes the following steps:

[0046] (1) Mix the raw materials Na2Se powder, Sb2Se3 powder, Sn powder and Se powder evenly in a molar ratio of 0.3:0.1:0.4:0.2;

[0047] (2) The uniformly mixed raw materials were vacuum-sealed in a quartz tube, and then the quartz tube was placed in a swing furnace and melted at 950°C for 2 hours. The quartz tube was then quenched with compressed air for 0.5 minutes, followed by annealing at 200°C for 8 hours. After furnace cooling, the quartz tube was opened to obtain Na. 0.3 Sb 0.1 Sn 0.2 Se 0.4 Bulk chalcogenide glass materials;

[0048] (3) Put Na 0.3 Sb 0.1 Sn 0.2 Se 0.4 The bulk chalcogenide glass material is cut into cuboids and its top and bottom surfaces are polished.

[0049] Will Na 0.3 Sb 0.1 Sn 0.2 Se 0.4 Bulk chalcogenide glass material is placed on an insulating pad, in Na 0.3 Sb 0.1 Sn 0.2 Se 0.4A conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and then an electrode is attached to the surface of the conductive silver paste layer. The electrode is connected to a 4.5V voltage through a wire.

[0050] Na prepared in Example 3 0.3 Sb 0.1 Sn 0.2 Se 0.4 The properties of bulk chalcogenide glass materials are as follows:

[0051] The ionic conductivity at room temperature is 0.007 S / cm;

[0052] Mechanical properties of Na 0.3 Sb 0.1 Sn 0.2 Se 0.4 It is in a glassy state, and after its upper and lower surfaces are polished, the thickness of the bulk material is 0.5mm, which has good light transmission ability;

[0053] Gradient refractive index: Maximum refractive index difference Δn = 0.09.

[0054] Example 4: Electric field controlled gradient refractive index K 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 A method for preparing chalcogenide glass materials includes the following steps:

[0055] (1) Mix the raw materials K2S powder, As powder, Ge2S powder, S powder and Te powder evenly in a molar ratio of 0.23:0.3:0.23:0.24:0.08;

[0056] (2) The uniformly mixed raw materials were vacuum-sealed in a quartz tube, and then the quartz tube was placed in a swing furnace and melted at 800℃ for 24 hours. Then, the quartz tube was quenched with compressed air for 0.5 minutes, and then annealed at 350℃ for 10 hours. After cooling in the furnace, the quartz tube was opened to obtain K. 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 Bulk chalcogenide glass materials;

[0057] (3) K 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 The bulk chalcogenide glass material is cut into cuboids and its top and bottom surfaces are polished.

[0058] K 0.23 As 0.15 Ge0.23 S 0.35 Te 0.04 Bulk chalcogenide glass material is placed on an insulating pad, at K 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 A conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and then an electrode is attached to the surface of the conductive silver paste layer. The electrode is connected to a 5V voltage via a wire.

[0059] K prepared in Example 4 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 The properties of bulk chalcogenide glass materials are as follows:

[0060] The ionic conductivity at room temperature is 0.009 S / cm;

[0061] Mechanical properties: K 0.23 As 0.15 Ge 0.23 S 0.35 Te 0.04 It is in a glassy state, and after its upper and lower surfaces are polished, the thickness of the bulk material is 0.5mm, which has good light transmission ability;

[0062] Gradient refractive index: Maximum refractive index difference Δn = 0.1.

Claims

1. An electric field-controlled gradient refractive index chalcogenide glass material, characterized in that, This chalcogenide glass material is composed of three elements: A, M, and X. Element A is selected from at least one of Li, Na, K, and Ag; element M is selected from at least one of B, Si, Ge, Sn, P, As, Ga, and Sb; and element X is selected from at least one of O, S, Se, and Te. The molar percentage of element A is 10%–80%, the molar percentage of element M is 5%–50%, and the molar percentage of element X is 10%–50%. The sum of the molar percentages of elements A, M, and X is 100%. The preparation method of this chalcogenide glass material includes the following steps: (1) Based on the determined molar percentage of each element in the chalcogenide glass material, calculate and weigh each raw material, and then mix the raw materials evenly. (2) Vacuum seal the uniformly mixed raw materials in a quartz tube, then place the quartz tube in a swing furnace and melt it at 250℃~950℃ for 1h~40h. Then quench the quartz tube with compressed air for 0.5min~3min, and then anneal it at 150℃~350℃ for 5h~30h. After cooling with the furnace, open the quartz tube to obtain the bulk chalcogenide glass material. (3) Cut and polish the bulk chalcogenide glass material into the desired shape.

2. The electric field-controlled gradient refractive index chalcogenide glass material according to claim 1, characterized in that, In step (2), the quartz tube is melted at 450℃~850℃ for 10h~25h, then quenched with compressed air for 1min~2min, and then annealed at 200℃~300℃ for 10h~20h.

3. The method for controlling the gradient refractive index of chalcogenide glass materials under electric field control as described in claim 1, characterized in that, By adding conductive units to the polished surface of bulk chalcogenide glass material, an external electric field of 0.05V to 10V is applied to the bulk chalcogenide glass material through the conductive units, thereby achieving a gradient refractive index with a maximum refractive index difference Δn of 0.

1.

4. The method for controlling the gradient refractive index of chalcogenide glass materials under electric field control according to claim 3, characterized in that, The conductive unit consists of a conductive silver paste layer and an electrode. The conductive silver paste layer is coated on the polished surface of the bulk chalcogenide glass material, and the electrode is attached to the surface of the conductive silver paste layer. The electrode is externally connected to a voltage of 0.05V to 10V.

5. The method for controlling the gradient refractive index of chalcogenide glass materials under electric field control according to claim 3, characterized in that, The voltage of the external electric field applied to the bulk chalcogenide glass material through the conductive unit is 0.1V to 5V.

Citation Information

Patent Citations

  • Preparation method of ultra-micro lens with periodic micro-nano structure and gradient refractive index by adopting grid electrode micro thermal polarization printing

    CN113391383A